Idiopathic Inflammatory Myopathies - Vencovský, Jiří; Alexanderson, Helene; Lundberg, Ingrid E (Rheumatic diseases clinics of North America, 2019)
Major advances have been made in the field of idiopathic inflammatory myopathies (IIM), or myositis, that are likely to facilitate development of new therapeutic strategies that have not yet been applied in this group of diseases. These advances include new classification criteria to better identify the patients with IIM, detection of several new myositis-specific autoantibodies that facilitates subgrouping of patients into more specific clinical phenotypes, development of outcome measures for disease activity, and new response criteria. We have learned from clinical studies that exercise is an important part of treatment and that pharmacologic treatment should be combined with exercise.
Keywords: Humans; Antirheumatic Agents; Autoantibodies; Treatment; Severity of Illness Index; Symptom Assessment; Exercise; Target; autoprotilátky; stupeň závažnosti nemoci; antirevmatika; Patient Care Management; určení symptomu; Criteria; Myositis; myozitida; lidé; management péče o pacienta